Pentingnya Pendidikan Etika Digital Dalam Konteks SDGs 2030 - Firda Laila Syahda; Yuniaridha Nur’aisyah; Ichsan Fauzi Rachman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to delve into the significant role of Digital Ethics Education in the context of achieving the Sustainable Development Goals (SDGs) 2030. The background of this research is based on the rapid transformation in the digital era that has influenced various aspects of life, including education. Digital ethics not only encompasses rules of conduct in the use of social media but also values related to technology. The integration of digital ethics education with the SDGs 2030 is expected to foster a positive attitude towards technology, instill a sense of online responsibility, and develop critical thinking skills in the digital world. The research method used is library research, involving an in-depth analysis of various primary sources such as books, scientific journals, articles, and related documents. This study also involves a review of 16 scientific journals to deepen the understanding of digital ethics, education, and the SDGs 2030. Through observation and analysis of various reference sources, this research highlights the importance of digital ethics education in achieving sustainable development goals. The results of the study indicate that digital ethics education plays a crucial role in shaping an intelligent, enlightened, and productive generation in the digital era. In conclusion, enhancing the quality of education with a focus on ethical and moral values is essential to create a digitally literate and ethical society, thereby contributing positively to achieving the SDGs 2030 and moving towards a sustainable future for all individuals